2021
DOI: 10.1002/jbt.22843
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity, antioxidant, and marker enzyme assessment of swertiamarin in zebrafish (Danio rerio)

Abstract: A secoiridoid glycoside called swertiamarin has been widely used as a herbal medicine for many decades. In particular, swertiamarin from the Enicostema axillare herb has been used as a multipurpose drug to treat innumerable health problems. As this medicine is consumed orally, its toxicity level should be determined. To examine the safety of this compound, toxicology work was done in zebrafish, and this is the first report to describe swertiamarin toxicity in zebrafish. Zebrafish embryos were used in this swer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 67 publications
0
6
0
2
Order By: Relevance
“…Plants are a source of nature's most important secondary metabolites, the generation of extracts and their application in treatments or to identify new specific substances used to make medicines, the potential of these extracts is of great importance for the food and pharmaceutical industry. (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) In the first phase of the metabolite revision, it was observed that in several studies plant extracts were used for both antioxidant and anti-inflammatory activity tests, five of the reviewed studies used extracts, mainly freeze-dried, Boeri et al (14) and Nguyen T. (31) performed an extraction in organic solvents that are toxic to zebrafish, so it is necessary to remove these solvents before using the compound, while Pradeep et al (32) used the fraction in ethanol, Conducting tests to determine oxidative stress directly with the extract; this indicates that the status of the metabolite's final product is a factor that can influence the antioxidant activity and in vivo analysis of the model.…”
Section: Plant Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants are a source of nature's most important secondary metabolites, the generation of extracts and their application in treatments or to identify new specific substances used to make medicines, the potential of these extracts is of great importance for the food and pharmaceutical industry. (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) In the first phase of the metabolite revision, it was observed that in several studies plant extracts were used for both antioxidant and anti-inflammatory activity tests, five of the reviewed studies used extracts, mainly freeze-dried, Boeri et al (14) and Nguyen T. (31) performed an extraction in organic solvents that are toxic to zebrafish, so it is necessary to remove these solvents before using the compound, while Pradeep et al (32) used the fraction in ethanol, Conducting tests to determine oxidative stress directly with the extract; this indicates that the status of the metabolite's final product is a factor that can influence the antioxidant activity and in vivo analysis of the model.…”
Section: Plant Extractsmentioning
confidence: 99%
“…Fertilized eggs were used in the early stages of development, with Mohamad Shariff et al (19) , Pradeep et al (18) and Boeri et al (14) , at 1-hour post-fertilization (h.d.f), (14,16,21) between 2 and 6 h.p.f. (20) It occupied fish of 10 h.p.f, while, in the other studies embryos of 1-and 3-days postfertilization was used (d.p.f).…”
Section: Plant Extractsmentioning
confidence: 99%
“…Otro de los métodos más comunes en estos estudios, fueron las cuantificaciones de actividad enzimática, (Perumal et al, 2021) realizaron varios análisis para enzimas CAT (catalasa), SOD (superóxido dismutasa), GSH (glutatión reducido), GPx (glutatión peroxidasa), GST (glutatión S-transferasa), además de peroxidación lipídica, si bien, en este grupo de metabolitos no se observó una gran presencia de estos estudios, en los otros grupos se incrementa la importancia de los mismos.…”
Section: Extractos Vegetalesunclassified
“…Se usó huevos fecundados en etapas tempranas de desarrollo, con (Mohamad Shariff et al, 2020), (Pradeep et al, 2019) y (Boeri et al, 2020) a 1 hora post fertilización (h.d.f), (Perumal et al, 2021), (Wang & Liu, 2020), (Boeri et al, 2020) entre 2 y 6 h.p.f, (Udaya et al, 2020) ocupó peces de 10 h.p.f, mientras que, en los otros estudios se usó embriones de 1 y 3 días post fertilización (d.p.f). Mientras que en ensayos para estrés oxidativo solo en tres estudios se emplearon oxidantes, AAPH (dihidrocloruro de 2,2'-azobis (2amidinopropano) con (Boeri et al, 2020), sulfato de cobre con (Nguyen et al, 2020)y oxazolona con (Poornima et al, 2019).…”
Section: Extractos Vegetalesunclassified
“…30 Lipid peroxidation (LPO) is an antioxidant which is involved in the oxidation process of phospholipids during the antioxidant defence process. 31 Thus, antioxidants are widely used as biological health indicators of aquatic inhabitants. Likewise, the toxic effect of chemicals on tissues could be evaluated by assessing histopathology.…”
Section: Introductionmentioning
confidence: 99%